Two mutations in TUBB8 cause developmental arrest in human oocytes and early embryos - Cao, Tianqi; Guo, Jing; Xu, Yan; Lin, Xiufeng; Deng, Weifen; Cheng, Lizi; Zhao, Huan; Jiang, Shan; Gao, Min; Huang, Junjiu; Xu, Yanwen (Reproductive biomedicine online, 2021)
How can the effect of genetic mutations that may cause primary female infertility be evaluated? Patients and their family members underwent whole-exome sequencing and Sanger sequencing to detect the infertility-causing gene and inheritance pattern. To study the function of mutant proteins in vitro, vectors containing wild-type or mutant TUBB8 cDNA were constructed for transient expression in HeLa cells, and in-vitro transcribed mRNA were used for microinjection in germinal vesicle-stage mouse oocytes. Immunofluorescence staining was used to observe the microtubule structure in HeLa cells or meiotic spindle in mouse oocytes. A maternally inherited TUBB8 (Tubulin beta 8 class VIII) mutation (NM_177987.2: c. 959G>A: p. R320H) and a previously reported (NM_177987.2: c. 161C>T: p. A54V) recessive mutation from two infertile female patients were identified. The oocytes from the patient carrying p.A54V mutation failed fertilization, whereas oocytes with p.R320H mutation could be fertilized but showed heavy fragmentation during early development. In vitro, functional assays showed that p. A54V mutant disrupted the microtubule structure in HeLa cells (49.3% of transfected cells) and caused large polar body extrusion in mouse oocytes (27.5%), whereas the p.R320H mutant caused a higher abnormal rate (69.7%) in cultured cells and arrested mouse oocytes at meiosis I (38.7%). Two TUBB8 mutations (p.A54V and p.R320H) were identified and their pathogeny was confirmed by in-vitro functional assays.